Re-presenting layers of history in the "natural landscape": an architectural exposition of the Silvermine Reservoir - Jordi, Rupert Benjamin (School of Architecture, Planning and Geomatics, 2017)
The story of how a particular place came to be is more than the knowledge of a chronology of events; it is intimately part of our experience of that place. By knowing even a little of the history of a place, our perception of that place is transformed. In Historical Ground, John Dixon Hunt uses the term historical ground to refer to the notion that memories, tales, myths, and historical artefacts adhere to a place. The question Hunt then asks is how an existing site, and its tales, may be told through the medium of architecture, or landscape architecture. The idea that each site accumulates histories which may be revealed through architecture, is the basis for my own investigation. In the context of the Cape Peninsula mountain range, I am interested in seeking out and revealing particular historical narratives through the medium of architectural intervention. This report traces the journey of my design research project from my broader interests in the history of the mountain range; through the clarification of my architectural intentions; to my initial siting and programming strategies; and finally to my first ideas about making architecture in this context. I would describe this process as one of walking, finding, linking, and ultimately responding. This report introduces several key elements which underpin my research project. These elements (or layers) are: mountain (my general site of inquiry); pathways (how movement is linked to memory and meaning); earth (a technical study of the encounter between earth and architecture); fire (and its effects on the landscape); water (a resource with a story); and the wall (an historical piece of infrastructure). Each of these elements guides the reader through my research process and highlights certain found histories and artefacts along the way. As each element is presented, my research hones in on one particular place in the landscape, which is ultimately the site of my design investigation. This site, with the addition of a final artefact (a found brief), becomes the site of an architectural proposition which seeks to engage and link all of these elements together.